Effects of rumen-protected fat on changes of metabolites and reproductive genes in testes of Malin rams - Ismail, A.; Muhammad, A. I.; Kee, L. T.; Chwen, L. T.; Samsudin, A. A. (Diponegoro University, 2023)
The effects of RPF on metabolites and reproductive genes in testes of Malin ram was investigated. Twenty Malin rams (36.6kg ± 5.57 kg of bodyweight), were subjected to four dietary treatments; A: basal diet without rumen-protected fat (RPF), B; basal diet with 2% prilled fat, C; basal diet with 2% calcium salt and D; basal diet with 2% canola oil. At the end of the experiment four out of five animals from each group were slaughtered. The testes were excised for metabolites and gene expression stud-ies. The genes tested were associated to testes development and spermatogenesis (ODF1, SERPINA10, CatSper4, AdipoR2 and DAZL). Feeding RPF with calcium salt (Treatment C) has resulted in the up-regulation more than two folds in all reproductive genes. There were metabolites changes occurred between the groups and identified 44 important putative metabolites present in the testes. In conclu-sion, feeding of RPF to the animals as a source of energy has up-regulated the genes and identified the metabolites involve in the male reproductive tissues and activities.